2019
DOI: 10.1093/ecco-jcc/jjz128
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytoclastic Vasculitis Related to Ustekinumab in a Crohn’s Disease Patient: First Case Report and Literature Review

Abstract: Leukocytoclastic vasculitis is a single-organ, skin-isolated small vessel vasculitis. It can be a side effect of many common drugs, including biological agents. Unlike with other drugs, leukocytoclastic vasculitis induced by biological agents may have a prolonged latency period. We report the first case of ustekinumab-induced leukocytoclastic vasculitis in a patient with inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
10
0
2
Order By: Relevance
“…Real world data from the ENEIDA registry, the GETAID cohort and a US population were consistent with the known safety profile of UST (77)(78)(79). Three cases of leukocytoclastic vasculitis related to UST have been reported (79,95,96). To date, there are no data on safety for Risankizumab, Brazikumab and Guselkumab in UC.…”
Section: Anti-il23 P19supporting
confidence: 54%
“…Real world data from the ENEIDA registry, the GETAID cohort and a US population were consistent with the known safety profile of UST (77)(78)(79). Three cases of leukocytoclastic vasculitis related to UST have been reported (79,95,96). To date, there are no data on safety for Risankizumab, Brazikumab and Guselkumab in UC.…”
Section: Anti-il23 P19supporting
confidence: 54%
“…These included the development of a Mycobacterium abscessus soft tissue infection, 24 malignant melanoma in a patient with dysplastic nevus syndrome, 25 and leukocytoclastic vasculitis. 26 In a long-term efficacy and safety study of ustekinumab for Crohn's disease, ustekinumab was found to have a favorable safety profile, comparable to that of placebo. Injection site reactions were low, and no serious opportunistic infections were recorded during the extension period.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the patients in this review developed LCV as reactive manifestation of UC (95%), and only one patient (5%) developed LCV as a consequence of anti-tumor necrosis factor (TNF-alfa) therapy [12]. This finding is strikingly different from patients with LCV and CD, where LCV attributed to IBD therapy (most commonly infliximab and adalimumab) was found in 60% of patients [8,41]. In one of the cases, a streptococcal infection preceded both rash occurrence and UC symptoms.…”
Section: Discussionmentioning
confidence: 76%